EVALUASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI PADA BIRO OTONOMI DAERAH SEKRETARIAT DAERAH PROVINSI SULAWESI TENGAH) - Lindayani, Lindayani (Katalogis, 2018)
The purpose of this study was to determine why the implementation of the Government Performance Accountability System in the Autonomous Region Bureau of the Regional Secretariat provinceCentral of Sulawesi has not been effective, which in the review based on a theoretical model of policy evaluation Daniel Stuffleabem using variables: 1). Context evaluation (evaluation of the context), 2). Input evaluation (evaluation of the inputs), 3). Process evaluation (evaluation of the process) and 4). Product Evaluation (evaluation of results). This type of research used by decision-informant Qualitative by purposive sampling and the number of selected informants 6 with the data collection techniques, 1). Observation, 2). Interviews, 3) Documentation. By analyzing of all the interviews. Research shows that the evaluation of the implementation of Government Performance Accountability System in the Autonomous Region Bureau of the Regional Secretariat province Central of Sulawesi ineffective by Central of Sulawesi Governor Regulation No. 38 Year 2015 on SAKIP. Judging from the four evaluation model proposed by Daniel Stuffleabem, criteria that goes well that is input evaluation or evaluation of the input that is associated with the legislation used in the preparation and implementation of SAKIP. While the criteria are not optimal in the evaluation of Government Performance Accountability System namely Context evaluation (evaluation of the context), Process evaluation (evaluation of the process) and Product Evaluation (evaluation of results). effectiveness and responsiveness due to the alignment between planning documents in a single entity not connected properly, there is still sectoral ego of each part in budget allocation and target-output performance indicators is still not the outcome.